Self-Regulated Learning Phases on Reading Comprehension: Students’ Perception - Ratih Laily Nurjanah (Universitas PGRI Semarang, 2021)
This study addresses the gaps shown by researches related to importance of reading strategies to create the generation of independent university students that can be started by implementing self-regulated learning strategy with its 3 phases guided with proper instructions from lecturer so students are kept working on track while building their reading comprehension skill. Related to the SRL phases, it is important to get students’ perception on the strategy so lecturer can decide which phase needs more attention. The objectives of this study are; to observe students’ perception on each phase of self-regulated learning strategy and which phase of self-regulated learning strategy is the easiest to follow by students. It is a qualitative research with closed-questions questionnaire distributed to students after applying the self-regulated learning phases on reading comprehension activity. 15 of 20 students agreed that time-allotment helps them to finish the tasks on time in Forethought and Planning phase. 12 students disagreed that writing the journal regularly in Monitoring phase could help them choose which strategy worked best for them. The first half could not decide whether they can get their strengths and weaknesses by evaluating their performance in Reflection phase and the other half agreed on the statement. 20 students agreed that the Forethought and Planning phase was easy to follow. 15 students disagreed that Performance Monitoring was easy to follow. 13 students strongly disagreed that this phase was easy. The Forethought and Planning Phase of SRL was the easiest to follow.